Solvent tolerant lipases: a review - Salihu, Aliyu; Alam, Md Zahangir (Elsevier, 2015)
Lipases have proven to be useful in different hydrolytic and synthetic reactions of industrial importance. Microbial strains from natural and extreme environments produce lipases with unique characteristics. The ability of lipase to withstand different environmental conditions during reactions, including temperature and pH, is essential. Solvent systems tend to affect lipase-catalyzed reactions, and thus the careful selection of both the medium and the lipase source is necessary. This review considers different solvent systems used in lipase-catalyzed reactions and some of the enzymatic properties required for function. Other properties of interest besides enzyme activity include tolerance, stability and compatibility to dif- ferent reaction media, such as acid, alkaline, salt, organic solvents and other compatible solvents (ionic liquids and detergents). For lipase to be used in a detergent, its thermostability and alkaline tolerance must be well pronounced. In addition, organic solvent stability plays an essential role in employing lipases for biodiesel production. Thus, the selection of the lipase for each application is based on speciﬁcity and stability in different solvent systems, which gives lipases many potential applications in aqueous and non-aqueous biocatalysis.